Corneal Endothelial Cell Density and Retinal Nerve Fiber Layer in Primary Open Angle Glaucoma, Normal Tension Glaucoma and Ocular Hypertension: Doi: https://doi.org/10.36351/pjo.v37i1.1062 - Khan, Bakht Samar; Nawaz, Abid; Shami, Lyla; Irshad, Zubaida; Ahmad, Mansoor (Pakistan Journal of Ophthalmology, 2020)
Purpose: To compare the corneal endothelial cell density (CED) and retinal nerve fiber layer thickness (RNFL) in primary open angle glaucoma (POAG), normal tension glaucoma (NTG) and ocular hypertension (OHT). Study Design: Cross sectional Observational study. Place and Duration of Study: Khyber Teaching Hospital, Peshawar, from April 2016 to March 2018. Methods: Patients having a single IOP reading of 21 mm Hg or more with glaucomatous cupping, visual field defect and open angle were labeled as POAG. Patients with IOP less than 21 mm Hg with same findings were labeled as NTG. Those eyes with raised IOP (more than 21 mm Hg), normal visual field and optic disc were labeled as OHT. Corneal endothelial cell count, central corneal thickness and retinal nerve fiber layer (RNFL) thickness were measured in patients of POAG, NTG and OHT. These were compared with normal age matched values. Results: Thirty eyes with POAG, 10 with OHT and 10 with NTG were included in the study. In patients with POAG there was 13.33% CED and 27.7% mean RNFL thickness loss. In patients with NTG there was 3.06% CED and 34.04% mean RNFL thickness loss. In patients with OHT there was 7.17% CED and 5.5% mean RNFL thickness loss. Conclusion: The loss of both RNFL thickness and CED occurs in POAG, OHT and NTG. Severe loss of RNFL thickness occurs in POAG and NTG while severe loss of CED occurs in POAG and OHT. Mild loss of RNFL thickness occurs in OHT while mild loss of CED occurs in NTG. Key Words: Specular Microscopy, Optical Coherence Tomography, Nerve Fiber Layer, Open Angle Glaucoma, Ocular Hypertension.